2013
DOI: 10.1111/jgh.12091
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenviroment and hepatocellular carcinoma metastasis

Abstract: The cross talk between tumor cells and the surrounding peritumoral stroma has been extensively studied as a dynamic system involving the processes of hepatocarcinogenesis, tumor invasion, and metastasis in recent few decades. Besides hepatocytes, liver tumor microenvironments are generally classified into cellular and noncellular components, including hepatic stellate cells, fibroblasts, immune, endothelial, mesenchymal stem cells, together with growth factors, cytokines, extracellular matrix, hormone as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 83 publications
1
61
0
Order By: Relevance
“…However, the sensitivity to sorafenib after development of resistance can partially be restored using PI3K/Akt-or BCRP/Hedgehog-inhibitors in vitro. In addition to hepatocytes, noncellular tumor components may also play a role [49] . They manipulate hepatocellular carcinoma invasion and metastasis by facilitating epithelial-mesenchymal transition, increasing the proteolytic activity of matrix metalloproteinases, and regulating antitumor immunity.…”
Section: Epithelial-mesenchymal Transition and Sorafenib Resistancementioning
confidence: 99%
“…However, the sensitivity to sorafenib after development of resistance can partially be restored using PI3K/Akt-or BCRP/Hedgehog-inhibitors in vitro. In addition to hepatocytes, noncellular tumor components may also play a role [49] . They manipulate hepatocellular carcinoma invasion and metastasis by facilitating epithelial-mesenchymal transition, increasing the proteolytic activity of matrix metalloproteinases, and regulating antitumor immunity.…”
Section: Epithelial-mesenchymal Transition and Sorafenib Resistancementioning
confidence: 99%
“…118 High NK cell infiltration in tumor sites correlates with a better prognosis and improved survival. 11 NK cells express chemokine receptors, such as CCR2, CCR5, CXCR3 and CX3CR1, and can migrate to inflamed sites or to tumors in response to their respective chemokines. CXCR3 and CX3CR1 are key chemokine receptors responsible for NK cell migration to tumors.…”
Section: Nk Function and Chemokinesmentioning
confidence: 99%
“…It has been demonstrated that tumor-infiltrating immune cells play an important role in host immune defense against tumor progression in various cancers. [8][9][10][11] These observations seem to provide a reasonable treatment direction and impel an increasing number of researchers to focus on immune responses in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the most common liver cancer and has a very poor treatment outcome [1][2][3]. Nevertheless, although our understanding of the pathogenesis of HCC has significantly improved in the past years, the precise molecular basis underlying HCC cell growth and survival from chemotherapy remains not clarified [4].…”
Section: Introductionmentioning
confidence: 99%